2011
DOI: 10.1007/s13577-011-0008-1
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts have plasticity and potential utility for cell therapy

Abstract: Fibroblasts exist in the interstices of various organs as a component of connective tissue and are one of several types of somatic cells that have been well established in culture. They have been reported to undergo myogenic conversion and to induce the expression of genes associated with pluripotency. However, their own plasticity with regard to direct differentiation has scarcely been described. Here, we show that human fibroblasts are able to differentiate directly to all three germ layer derivatives. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…, Osonoi et al . ). In this study, the purpose was to highlight the nemosis process in dental pulp and lung fibroblasts spheroids to compare this type of cell death in these two cell populations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Osonoi et al . ). In this study, the purpose was to highlight the nemosis process in dental pulp and lung fibroblasts spheroids to compare this type of cell death in these two cell populations.…”
Section: Discussionmentioning
confidence: 97%
“…Fibroblasts are heterogeneous cells able to activate and to be involved in inflammation and immune reactions (Silzle et al 2004, Staquet et al 2008. These cells are known to have great plasticity and to be the predominant cell type in the dental pulp (Goldberg & Smith 2004, Goldberg et al 2008, Nakanishi et al 2011, Osonoi et al 2011. In this study, the purpose was to highlight the nemosis process in dental pulp and lung fibroblasts spheroids to compare this type of cell death in these two cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, this remains highly controversial especially because the functional properties of MSCs transdifferentiated into ectoderm and endoderm are not as expected. Similarly Osonoi et al [17] reported that human dermal fibroblasts are able to differentiate directly to all 3 germ layer derivatives that is, neurons (ectodermal), skeletal myocytes (mesodermal), and insulin-producing cells (endodermal). They exhibit nestin, desmin, and insulin when exposed to specific cocktail of growth factors.…”
Section: Introductionmentioning
confidence: 98%
“…MSCs self-renew and retain a multipotent differentiation capacity, whereas fibroblasts seem to display only limited, or no such, multipotent differentiation [2], although there is controversy in the literature over this issue. Indeed, it has been suggested that fibroblasts are able to differentiate [1,[3][4][5][6][7] and could be used in cell therapy [8]. Recently, Blasi et al [3] reported that fibroblasts may differentiate but lack anti-inflammatory and angiogenic capacity.…”
Section: Introductionmentioning
confidence: 99%